DETERMINAN SEKTOR PARIWISATA TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN BIAK NUMFOR TAHUN 2019-2023 - Marten, Rispa; Riantoro, Dedy; Sawaki, Magriet Ester (Fakultas Ekonomi dan Bisnis, Universitas Papua, 2025)
This study aims to analyze the effect of hotel tax, restaurant tax, and entertainment tax on Regional Original Income (PAD) in Biak Numfor Regency. This research is quantitative and uses 5-year time series data. The data used is secondary data sourced from the Central Statistics Agency (BPS) and the Directorate General of Fiscal Balance (DJPK). The data analysis method used in this study was multiple linear regression with the help of SPSS 25. The results show that: (1) Hotel tax has an impact on Biak Numfor Regency's Regional Original Income in 2019-2023. (2) Restaurant tax has an impact on Biak Numfor Regency's Regional Original Income in 2019-2023. (3) Entertainment tax has a positive impact on Biak Numfor Regency's Regional Original Income in 2019-2023. Simultaneously, hotel tax, restaurant tax, and entertainment tax have an impact on Biak Numfor Regency's Regional Original Income.